1973
DOI: 10.1002/cber.19731060937
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosidsynthesen, VIII. NMR‐ und CD‐Spektren von Pyrimidin‐nucleosiden und ihren 2‐Thioanaloga

Abstract: Es wird eine Reihe von Pyrimidin‐nucleosiden und ihren 2‐Thioanaloga NMR‐ und CD‐spektrometrisch untersucht. Beim Übergang von den Sauerstoff‐ zu den Schwefelverbindungen wird in der β‐Reihe das 1′‐H stark, die beiden 5′‐H schwach und, sofern vorhanden, das 2α′‐H mittelstark paramagnetisch verschoben. Bei den 2′‐Desoxyuridinen mit α‐Verknüpfung werden das 1′‐H, 2α′‐H, 2β′‐H, 3′‐H und 4′‐H mit in der angegebenen Reihenfolge abnehmender Stärke zu tieferem Feld verschoben, während die beiden 5′‐H sich nicht mehr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…12,27 Comparison of the H1′-H2′ coupling constants shows considerable differences, however. The β-thymidine values (7.0 and 7.0 Hz) 24 are similar to those for the α-anomer of the difluorotoluene nucleoside (7.6 and 7.6 Hz), and both resonances appear as pseudotriplets. Conversely, the α-anomer of thymidine has coupling constants (8.0 and 3.0 Hz) which are similar to those for the β-anomer of the difluorotoluene nucleoside (10.4 and 4.6 Hz), and these appear as doublets of doublets.…”
Section: The Anomeric Effect and Deoxyribose Conformationsupporting
confidence: 55%
See 2 more Smart Citations
“…12,27 Comparison of the H1′-H2′ coupling constants shows considerable differences, however. The β-thymidine values (7.0 and 7.0 Hz) 24 are similar to those for the α-anomer of the difluorotoluene nucleoside (7.6 and 7.6 Hz), and both resonances appear as pseudotriplets. Conversely, the α-anomer of thymidine has coupling constants (8.0 and 3.0 Hz) which are similar to those for the β-anomer of the difluorotoluene nucleoside (10.4 and 4.6 Hz), and these appear as doublets of doublets.…”
Section: The Anomeric Effect and Deoxyribose Conformationsupporting
confidence: 55%
“…12 By comparison, the α-anomers of the natural DNA N-nucleosides have considerably different coupling constants for this same H1′ resonance; for α-thymidine these are found to be 8.0 and 3.0 Hz, and the resonance appears as a doublet of doublets. 24 Virtually the same coupling constants are found for β-and α-deoxyadenosine as well. 25 This difference between the two isomers arises from the different dihedral angles which are present in the two anomeric isomers.…”
Section: The Anomeric Effect and Deoxyribose Conformationmentioning
confidence: 58%
See 1 more Smart Citation
“…We studied the H1'-H2' coupling constants for the two anomers of the isostere 18 and compared them to literature values for α-and β-thymidine. 33 In the literature it is observed that β-anomers of the natural deoxynucleosides give splitting patterns for H-1' which resemble a triplet, meaning the two coupling constants are similar. Interestingly, we observe that it is the opposite (α)-anomer of the isostere which appears as a triplet.…”
Section: The Anomeric Effect and Deoxyribose Conformationmentioning
confidence: 99%
“…Analysis of the NMR spectra of 6Me Ud in D 2 O pointed to the predominant base population in the syn -conformation [62]. The stereochemistry of 6-methyluridine was also investigated by physicochemical methods [6365] and in crystal [66] and the dominating syn base conformation around the glycosyl bond was established.…”
Section: Resultsmentioning
confidence: 99%